Structural variations in epsilon-type Al-Pd-(Mn, Fe) complex metallic alloy phases - Engel, Michael; Trebin, Hans-Rainer; Heggen, Marc; Balanetskyy, Sergiy; Feuerbacher, Michael (Philosophical Magazine, 2008)
Structural modifications in complex metallic epsilon-Al-Pd-(Mn, Fe) samples were studied by means of transmission electron microscopy. The modifications were observed in the vicinity of metadislocations and at phase boundaries. They are determined by the density and inclination of phason planes. In the vicinity of metadislocations and at an epsilon(6)-epsilon(28) phase boundary, new monoclinic E-type structures appear locally, which had not been detected as bulk phases in Al-Pd-(Mn, Fe) previously. The present work points out the close entanglement between defects, i.e. metadislocations and phason planes, and structural modifications in E-type complex metallic alloys. An extended classification of E-type phases including monoclinic phases is presented on the basis of two different tiling descriptions.